KIDNAPPING AS AN OBJECT OF APPLIED RESEARCH - Mikhail V. Karmanov (Статистика и экономика)
Modern society is not capable to get rid of such a serious problem as the kidnapping. Its solution at least in the future is difcult to imagine without a comprehensive quantitative characterization of kidnapping, which is impossible without reliable statistical information. In this context of great scientic and practical interest is the improvement of the methodology of practical research kidnapping as the negative socio-economic phenomena.